SSR Mapping of QTLs Conferring Cold Tolerance in an Interspecific Cross of Tomato - Yang Liu; Tengxia Zhou; Haiyan Ge; Wen Pang; Lijie Gao; Li Ren; Huoying Chen (International Journal of Genomics)
A population of 146 RILs (Recombinant Inbred Line) was derived from the cross between a cold-sensitive cultivated Solanum lycopersicum L. XF98-7 and a cold-tolerant wild Solanum pimpinellifolium LA2184. Relative germination ratio (RGR) and chilling index (CI) were used to evaluate the cold tolerance of the parental lines and RILs. It was found that the RGR and CI were significantly different between S. lycopersicum XF98-7 and S. pimpinellifolium LA2184 under cold treatment, indicating that wild species was more adapted to chilling temperature. The continuous and normal distribution of RGR and CI in RIL population suggested that the trait of cold tolerance was a typically quantitative trait controlled by multigenes. The molecular linkage map was constructed by using 120 simple-sequence repeat (SSR) markers, resulting in 15 linkage groups, with a total distance of 256.8 cM and average interval of 2.14 cM. Five QTLs controlling RGR and four QTLs for CI were detected with genetic contribution ranging from 0.95% to 19.55%. Thus, the nine QTLs will provide references for further fine position mapping for cold tolerance. The polymorphic markers could be used as a way of indirectly selecting the plant trait of interest and would promote developing new tomato variety by marker-assisted selection.